Narrative Constructions in Instagram Feeds on COVID-19 Pandemics - Kevin Susanto Pokhan (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
This study was done to investigate how narratives on issues or topics of serious concern focusing on COVID-19 pandemic, dated back from April to December 2020, were constructed in the selected Instagram feeds and the existing patterns of regularities could be identified in the narratives. To answer these two research questions, the writer uses theories from Labov (1967, as cited in De Fina & Johnstone, 2015) about narrative construction as the theory. The subjects of this study were the Instagram feeds of three influencers, namely: dr. Tirta, dr. Reisa and dr. Sonia. The findings showed that in general, all of the three doctors’ narratives have five narrative elements: abstract, orientation, complicating action, resolution, and coda. However, two of dr. Sonia's narratives have four narrative elements: abstract, orientation, complicating action and coda. This is due to dr. Sonia's narratives that have less lines than dr. Reisa's narratives.Keyword: Narrative, Instagram, Instagram feeds, COVID-19, Pandemic.